True Special Education Leadership? Better Avoid This in Your Leadership - Mohdnorazmi Nordin; Yasninurul Huda Mohd Yassin; Jabil Mapjabil; Norzanariah Talib; Mohdhasifabd Hamid; Norzeha Othman (International Journal of Aquatic Science, 2021)
Implementing effective leadership for special education requires a higher level of effort than educational leadership in the mainstream. As is well known, special education is a unique branch of education with its citizens consisting of special education teachers and students with diverse special needs. In addressing any problems in special education, leadership needs to exercise leadership more efficiently. As such, there are several things to avoid in the implementation of special education leadership. This study was conducted to explore certain aspects that should be avoided in implementing leadership in special education. This qualitative study uses interviews as a means of collecting data. A total of 20 special education teachers were involved in this study which was randomly selected in the district of Batu Pahat, Johor, Malaysia. The findings of the study show that special education leaders need to avoid five things in their leadership namely biased, overly assertive, untrustworthy, autocratic and punitive. It is hoped that this brief study can help future researchers in conducting further research related to this issue.